A Selection of hymns and spiritual songs: in two parts ... designed (especially the former part) for the use of congregations as an appendix to Dr. Watts's Psalms and hymns - Parkinson, William (Benson collection of hymnals and hymnology, 1809)
Part I. Containing the hymns. -- Part. II. Containing the songs.